Penggunaan Model PERMA dalam Komunikasi Pastoral Care untuk Pasien Kanker dan Cuci Darah: Studi Kasus di Rumah Sakit Panti Rapih Yogyakarta - Immanuelle, Oei Tiara Azalia; Romo Yustinus Joko Wahyu Yuniarto; Gregorius Daru Wijoyoko; Fr. Wuriningsih (Pastoralia Jurnal Penelitian Dosen, 2025)
This study analyzes the implementation of the positive psychology theory of the PERMA model (Positive Emotion, Engagement, Relationship, Meaning, Achievement) in the context of Pastoral Care (PC) communication in cancer and dialysis patients at Panti Rapih Hospital, Yogyakarta. Using a qualitative-descriptive approach, this study examines how PERMA elements are integrated into pastoral care to improve patients' spiritual and psychological well-being. The results showed that pastoral communication implementing the PERMA model successfully facilitated positive emotions, active involvement, strengthening relationships, finding meaning, and personal achievement for patients. These findings emphasize the importance of integrating spiritual care in holistic care for patients with chronic diseases and provide an empirical basis for the development of a positive psychology-based pastoral communication approach in health facilities.